Coinheritance of HbO Arab/β0-thalassemia with Severe Manifestation in Newborn - Kalai, Miniar; Moumni, Imen; Ouragini, Houyem; Chaouechi, Dorra; Boudriga, Imen; Menif, Samia (American Journal of Perinatology, 2022)
Objective In this study, we report a Tunisian newborn boy referred for neonatal hemolytic anemia with yellowish skin and enlarged spleen due to coinheritance of hemoglobin O (HbO) Arab and β-thalassemia.Study Design Hematological parameters were collected using an automated blood cell counter. The amounts of Hb fractions were measured by capillary electrophoresis of Hb. Amplification and sequencing of the HBB gene were performed by Sanger's method.Results Family study and genetic analysis revealed that the proband was a carrier of two hemoglobinopathies: HbO Arab and β0-thalassemia.Conclusion The coexistence of these two pathologies complicated the general state of the newborn boy and led to a severe anemia at birth.Key Points
Keywords: HbO Arab/β0-thalassemia; newborn; anemia